2020
DOI: 10.1002/isd2.12159
|View full text |Cite
|
Sign up to set email alerts
|

An empirical analysis of the use of agricultural mobile applications among smallholder farmers in Myanmar

Abstract: Mobile phone applications (apps) designed to assist smallholder farmers improve decision‐making have been revolutionizing the agriculture sector. These apps offer solutions to farmer information needs by providing weather information, crop market trends, pest and disease damage identification, and advice on pesticide and fertilizer use. They also facilitate interaction with fellow farmers, extension workers and other stakeholders in the value chain who are interested in information exchange. Much previous rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…phone calls, chat apps) over externally-driven DETs (e.g. voice message advisory services, SMS advisory services and specialised agri-apps) ( Krell et al, 2021 ; Thar et al, 2021a ; Voutier et al, 2020 ; Munthali et al, 2018 ; Butt, 2015 ; Rasmussen et al, 2015 ). This becomes more understandable in view of the fifteen identified pitfalls ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…phone calls, chat apps) over externally-driven DETs (e.g. voice message advisory services, SMS advisory services and specialised agri-apps) ( Krell et al, 2021 ; Thar et al, 2021a ; Voutier et al, 2020 ; Munthali et al, 2018 ; Butt, 2015 ; Rasmussen et al, 2015 ). This becomes more understandable in view of the fifteen identified pitfalls ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Where it may be too soon for apps, it may be legitimate to explore alternative digital tools [89]. For example, the Myanmar cases corresponded with findings from a survey with Burmese farmers [34] and illustrated the need for multiple digital and non-digital channels to reach and engage with more farmers, which additionally widens the access to information for more user groups [90][91][92]. To build Southeast Asian farmers' trust in agricultural advisory apps, co-design requires that developers, programmers and software communities gain a better understanding of farmers' interactions on other social media platforms and how they adapt messaging apps and self-managed chatrooms for sharing forecasts, agroadvisories and knowledge [34,38,93], teaching themselves to build up e-literacy.…”
Section: The Passengers-smallholder Farmersmentioning
confidence: 99%
“…Literacy and e-literacy are not necessarily equivalent when it comes to being able to receive, understand, and be capable of acting on information provided through digital services [11,32]. Generally, men more than women, and younger more than older users are found using ICT among both farmers and agricultural extension staff [33,34], however, farmers' capability in interacting with phones varies [35]. For example, telecom companies adapt their services and rates to the most updated mobile phones, making services more expensive for those with old phones and poor internet connection [36].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sekabira et al [11] found that the gender, knowledge of ICT groups, and thought of ICTs benefit agriculture, family size, and land farmed previous season, affecting farmers' adoption of Information, Communication, and Technology (ICT) based market information services in Mayuge Smallholders, Uganda. Thar et al [12] revealed the determinant of mobile phone application-based internet in Myanmar Farmers, including age, education, number of crops, degree of mechanization, and market distance. Hoang [13] stated that age, market distance, income, gender, credit participation, and training participation influence the adoption of mobile phones for fruit marketing.…”
Section: Introductionmentioning
confidence: 99%